Women and property in early modern England - Erickson, Amy Louise (Routledge, 1993)
Àn impressive study.' - Germaine Greer. Amy Erickson combines legal, social and women's history in an imaginative and methodically interesting way to chart the limits and the contradictions of women as property owners.